GeneTransfection for Metastasis Research Using Animal Models. - Muschel, R; Hua, J (2001)
One means of testing a candidate gene for involvement in the metastatic process is to alter the expression of that gene in a tumor cell and then to test the metastatic potential of the altered cells. In designing such experiments, it is crucial to take into account the factor of tumor heterogeneity (1). Some cell lines or cultures contain highly heterogeneous populations in regard to metastasis. Upon cloning these cells, some clones will be highly metastatic, but others will not. Thus, selection of a clone itself might skew the results if only a few clones are evaluated. Furthermore, the use of pooled populations after transfection must be considered with caution because the population may contain cells with a variety of metastatic potentials. To avoid these problems, it is necessary to do a preliminary experiment in which the chosen parental cell is subcloned and the subclones are tested for metastatic behavior. If the subclones have a similar metastatic potential to the parental line, then it should be a suitable recipient for metastasis studies. If, however, there is considerable variability in the subclones, either the subclones can be tested for stability or another more stable cell line should be sought.